Molting of laying hens can activate AMPK- lipophagy - lipid metabolism pathway and improve intestinal digestion and absorption - Meiwei Lv; Chenxin Liu; Xiaowen Jiang; Ming Ge; Haibin Wang; Wenhui Yu (Poultry Science)
Poultry molting is a natural phenomenon, and process that improves the physiological function of laying hens. In this study, artificial intervention was used to induced molting (IM) in aged hens and improve their egg- laying performance. Jejunal lipophagy and lipid metabolism data were analyzed to elucidate the regulatory mechanisms by which the intestine affects egg production performance, particularly through the lens of digestion and absorption processes. Molting process in laying hens facilitated the regeneration of small intestinal villi following damage and shedding, while also reducing excess lipid accumulation within the intestine. Analyses of lipophagy and lipid metabolism-related factors revealed, increased the expression levels of genes and proteins, such as AMPK, FOXO1, TFEB, TFE3, PGC-1α and PPAR-α (P<0.05, P<0.01 and P<0.001). Serological analysis and detection of enzymes involved in digestion and absorption, showed upregulated expression of GLUT2, FABP (P<0.05 and P<0.001) and CD36 (P<0.01), and the activities of amylase, chymotrypsin and Lipase also increased significantly (P<0.05, P<0.01 and P<0.001). In conclusion, artificially IM activates the AMPK-lipophagy-lipid metabolism pathway to enhance intestinal digestion and absorption in laying hens. Our findings offer a theoretical framework for the intentional use of IM to promote a healthy state of digestion and absorption.